An Interactive Computational Strategy for Teaching the Analysis of Silo Structures in Civil Engineering - Saavedra-Flores, E; Yanez-Cart, S; Hinrechsen-Prieto, K (John Wiley and Sons Inc., 2019)
In this article, a Matlab-based software environment called Guide Silo Design (GSD) is proposed to help undergraduate students to better understand the complex phenomena involved in the analysis process of silo structures. The software is integrated with two commercial finite element softwares. These are the Open Application Programming Interface (OAPI) code in SAP2000 and the ANSYS Parametric Design Language (APDL) code in ANSYS. GSD allows civil engineering students to create a virtual simulation environment in which an effective and appropriate teaching-learning process can be experienced. The GSD environment is programmed in Matlab using a finite element-based mathematical framework. Furthermore, as the analysis of silo structures is highly relevant in real engineering projects, students can acquire fundamental knowledge for their future works as engineers. The present interactive virtual environment has great potential to improve the learning process of the analysis of silo structures. © 2019 Wiley Periodicals, Inc.